SOLUSI PELESTARIAN LINGKUNGAN DENGAN PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA MELALUI ECOENZYME - Amini, Zakiyah; Eviyati, R; Dwirayani, Dina (Universitas Muhammadiyah Mataram, 2022)
Environmental preservation activities can be started by households . The most common sources of waste are from household settlements , the composition is 75% consisting of organic waste and only 25% inorganic waste. The accumulation of garbage in TPS (Temporary Shelters ) creates an unpleasant sight and creates an unpleasant odor . Efforts to minimize the accumulation of waste is to separate organic waste and inorganic waste . Organic waste can be processed by the composting method of solid fertilizer or liquid fertilizer . In addition to the composting method , organic waste can be made eco enzyme . Eco enzyme is a solution to complex organic substances produced from the fermentation process of organic waste , sugar , and water . The implementation of this service activity is carried out by training in waste management through the manufacture of eco-enzymes for the Rukun Lestari Women Farmer Group , East Palimanan Village , Prapatan Block RT 13/ RW 05 Palimanan District , Cirebon Regency . The participants of the activity were very enthusiastic about the activities carried out because of the many benefits that can be obtained with the presence of eco enzymes , including as liquid organic fertilizer , organic pesticides, bathroom cleaners , hand sanitizers , and floor cleaners .